Reforming police education in Iceland: a comparative analysis of students’ competence valuations before and after the transition to university education - Bragason, Ólafur Örn (Policing and society, 2025)
Over the past few decades, police services worldwide have encountered significant challenges, notably due to technological advances, globalisation, and the rise of online crime. Iceland has responded to these changes by aiming to expand police students’ competences, notably through the implementation of an educational reform that involved closing the National Police Academy and establishing a blended learning university diploma programme for aspiring police officers. In this study, we investigated students’ reception of this development in knowledge and competences before and after the reform. We aimed to contribute to the professional education policy literature by using longitudinal data to compare students’ valuations of enduring and emerging competences before and after the transition from the police academy to the university level. The study participants were police students attending the Icelandic National Police Academy in 2011–2016 and the University of Akureyri in 2017–2023. The findings showed that university-level police students placed a higher value on both enduring and emerging competences than did those at the National Police Academy. This suggests that students at the university level regarded these competences as a more integral component of police education than academy students, despite most of them having worked as police officers during their education and already being integrated into an experience-based police culture. This study contributes to the literature on police education reform by providing empirical insights into how educational influence students’ valuations of key competences, with implications for professional education policy and practice.